2011
DOI: 10.1007/s10658-011-9805-3
|View full text |Cite
|
Sign up to set email alerts
|

Bemisia tabaci Biotype Q is present in Costa Rica

Abstract: Whiteflies are an insect group that comprises multiple species and biotypes, capable of affecting crops by phloem feeding, virus transmission and promotion of fungal colonization. The distribution of these pests is worldwide. In Costa Rica, a country located in the tropics, the most problematic whiteflies are Bemisia tabaci biotype B and Trialeurodes vaporariorum. In September 2009, two greenhouses in the Alfaro Ruiz region, northwest of the country's capital, San Jose, were surveyed as part of a larger effort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 18 publications
(23 reference statements)
0
11
0
1
Order By: Relevance
“…Our results are in agreement with those of Khan et al, (), who found that mountains can be physical barriers to the movement of insects and affect the occurrence of vector‐transmitted viruses. However, the global warming and the increasing spread of whiteflies in the country (Hilje & Morales, ; Guevara‐Coto et al, ) may result in a consistent expansion in begomovirus incidence and diversity, and thus in the occurrence of mixed infections.…”
Section: Discussionmentioning
confidence: 99%
“…Our results are in agreement with those of Khan et al, (), who found that mountains can be physical barriers to the movement of insects and affect the occurrence of vector‐transmitted viruses. However, the global warming and the increasing spread of whiteflies in the country (Hilje & Morales, ; Guevara‐Coto et al, ) may result in a consistent expansion in begomovirus incidence and diversity, and thus in the occurrence of mixed infections.…”
Section: Discussionmentioning
confidence: 99%
“…22,23 Since its discovery in Spain in 1997 24 and in Israel in 1999, 25 MED has caused severe crop damage in the Mediterranean Basin in both protected and open agriculture 26,27 and has exhibited an invasive ability arguably matched only by MEAM1. MED has recently been reported in Argentina and Uruguay, 28 China, 29 Costa Rica, 30 France, 31 Guatemala, 32 Japan, 33 Korea, 34 Mexico, 35 New Zealand, 36 Taiwan 37 and Tunisia, 38 as well as in the United States. 39 -42 In the United States, nuclear microsatellite markers exhibiting a high degree of concordance with mitochondrial markers uncovered a major east-west phylogeographic break within MED populations invading that country.…”
Section: Introductionmentioning
confidence: 99%
“…Introduction of the MEAM1 species in the Americas occurred in the late 1980s, and at present it is widely spread in all Latin American countries . In contrast, the MED species, which was originally described in Greece as Aleyrodes tabaci in 1889 by Gennadius, and was recently confirmed using molecular markers as the MED species, was only reported in the Americas in the United States, Mexico, Guatemala and more recently in Argentina, Uruguay and Costa Rica . In Brazil, B. tabaci populations belonging to the MEAM1 species are prevalent and have spread throughout the country, but two indigenous species, New World 1 (NW1) and New World 2 (NW2), have also been reported in different localities from Brazil and Latin America …”
Section: Introductionmentioning
confidence: 99%